An uncommon shape of epiglottis misleading as acute epiglottitis. (30th July 2012) - Sasaki, Toru; Nomura, Yasuyuki; Tsunoda, Koichi
Abstract : We report a case of a 31-year-old Japanese woman with an uncommon shape of epiglottis misleading as acute epiglottitis. She presented with high fever, arthralgia, general fatigue and strong throat pain. Laryngeal fiberscopy showed a markedly swollen epiglottis suggestive of acute epiglottitis, though she had no signs of asphyxia. A careful observation and detailed medical history ruled out acute epiglottitis. However, without clinical discretion, it might have been misinterpreted as acute epiglottitis. She was diagnosed later with Behçet's disease, which is reported to present pharyngeal stenosis. Two years later, a repeat laryngeal fiberscopy showed exactly the same appearance of the epiglottis, suggesting its shape to be permanent. The cause of this misleading shape of the epiglottis in this patient is yet unknown. For similar cases, a possibility of this kind of epiglottis should be considered before diagnosing as acute epiglottitis.